The Frequency of Ketoacidosis and Associated Factors at the Diagnosis of Type 1 Diabetes in Turkish Children: A Single-center Experience and Literature Review - Esen, Ihsan; Okdemir, Deniz (Galenos Yayincilik, 2021)
Aim: We aimed to investigate the frequency of diabetic ketoacidosis (DKA) and the associated factors at the time of diagnosis of type 1 diabetes (T1D) in children in a tertiary health center in Turkey, and to review previous studies conducted in Turkey. Materials and Methods: Data of 180 children with T1D (98 boys) aged 1 to 18 years were analyzed retrospectively. All children were consecutively diagnosed as having T1D at our pediatric endocrinology clinic between April 2016 and December 2019. To conduct a literature review, we screened PubMed, Google Scholar, Web of Science, and article reference lists as well as the proceedings of the national conferences organized by the Turkish Pediatric Endocrinology and Diabetes Society for the period until January 1st, 2020. Results: DKA was detected in 81 (45.0%) children with T1D at the time of diagnosis in this cohort. An association between DKA and high glycated hemoglobin (HbA1c) levels at the time of diagnosis was determined (p= 0.038). Furthermore, a relationship was also detected between severe DKA (pH<7.1 or serum bicarbonate <5 mmol/L) and children residing in rural areas, as well as mothers with education less than high school (p=0.003 and p=0.022, respectively). This study, together with a literature review of 49 other studies, identified that 4,037 (45.6%) of 8,837 children with newly diagnosed T1D presented with DKA at diagnosis between 1981 and 2019. Conclusion: In this cohort, presentation with DKA at the time of diagnosis of T1D in children was associated with high levels of HbA1c, and presentation with severe DKA was associated with rural life as well as low education levels of mothers. Almost half of all children with T1D presented with DKA in Turkey. There should be greater effort to increase awareness among society and health professionals for the early detection of T1D in children.
Keywords: Children; frequency; ketoacidosis; type 1 diabetes